Developing Community-Based Heritage Walking Tours for Local Economic Enhancement: A Case Study of Peneleh, Surabaya - Tiara Putry Gunawan; Bambang Suharto (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study addresses the gap between the high heritage potential and the limited community readiness in implementing Community-Based Tourism (CBT) in Kampung Peneleh, Surabaya. The objective is to analyze the potential and readiness of developing a community-based heritage walking tour as a strategy for enhancing the local economy. A descriptive qualitative approach was employed through in-depth interviews, field observations, and focus group discussions involving local communities and stakeholders. The findings reveal that although Peneleh possesses strong historical assets and place identity, its development is constrained by limited human resource capacity, weak tourism management, and insufficient stakeholder coordination. Unlike previous CBT studies that primarily emphasize participation as a success factor, this study highlights a critical gap between participation and actual capability, demonstrating that participation alone is insufficient without structured capacity building and product development. This research contributes to the literature by proposing an integrated perspective that combines human resource empowerment, experiential tourism product design (heritage walking tours), and collaborative governance as key determinants of sustainable CBT implementation. It also provides empirical evidence from an urban heritage context, which remains underexplored in prior CBT research dominated by rural tourism settings. The study concludes that strengthening community competencies and developing structured, experience-based tourism products are essential to generate inclusive and sustainable local economic benefits.